Intercepcion de patogenos fungosos en germoplasma importado de papa - Pueyo, M.=700 1 Hidalgo, I.; Perez, M.; Betancourt, L.; Abreu, J.
(Es, En)
Ilus., 7 ref.
Keywords: SOLANUM TUBEROSUM; ORGANISMOS PATOGENOS; HONGOS; FITOPATOLOGIA; PATOLOGIA DE LA SEMILLA; CUBA